Nasal insulin administration does not affect hepatic glucose production at systemic fasting insulin levels. Issue 4 (17th January 2019) - Plomgaard, Peter; Hansen, Jakob S.; Ingerslev, Bodil; Clemmesen, Jens O.; Secher, Niels H.; van Hall, Gerrit; Fritsche, Andreas; Weigert, Cora; Lehmann, Rainer; Häring, Hans‐Ulrich; Heni, Martin
Abstract : Aims: To evaluate the effects of brain insulin on endogenous glucose production in fasting humans, with a focus on hepatic glucose release by performing a randomized, placebo‐controlled, blinded, crossover experiment. Materials and methods: On two separate days, 2 H2 ‐glucose was infused to nine healthy lean men, and blood was sampled from the hepatic vein and a radial artery. On day 1, participants received 160 U human insulin through nasal spray, and on day 2 they received placebo spray, together with an intravenous insulin bolus to mimic spillover of nasal insulin to the circulation. Hepatic glucose fluxes and endogenous glucose production were calculated. Results: Plasma insulin concentrations were similar on the two study days, and no differences in whole‐body endogenous glucose production or hepato‐splanchnic glucose turnover were detected. Conclusions: Nasal administration of insulin does not influence whole‐body or hepatic glucose production in fasting humans. By contrast, pharmacological delivery of insulin to the brain might modulate insulin effectiveness in glucose‐producing tissue when circulating insulin levels are elevated; therefore, the metabolic consequences of brain insulin action appear to be dependent on metabolic prandial status.